Telehealth Innovations in Remote Healthcare Services Delivery Global Telehealth 2020 - Maeder, Anthony J.; Maeder, Anthony J.; Higa, Christina; Gough, Claire (SAGE Publications, 2021)
The need to promote academic activities in telehealth remains a high priority as the discipline expands into new areas of healthcare. Response during 2020 to the COVID-19 pandemic has provided an excellent example of the rapid diversification and impact attainable with telehealth, and may kindle a new momentum for accelerated service design and adoption processes in the future. This book, Telehealth Innovations in Remote Healthcare Services Delivery, is the tenth in the Global Telehealth series. Due to the prevailing COVID-19 pandemic and the restrictions placed on academic gatherings, the organizers issued a general call for contributions, with the intention of attracting a wide cross-section of contributions reflecting the breadth of different aspects of telehealth internationally. The resulting collection offers snapshots of research projects and studies of service experience from five continents, with an emphasis on delivering benefits in regional settings in keeping with the theme of the book$1 (Bs title. Articles range from descriptions of telehealth networks and clinical-service instances such as cardiac health, mental health and pathology, several in Pacific-rim settings, to more generic papers on the evolution of such services, as well as commentaries on innovative considerations for telehealth such as the emergence of the concept of virtual care, the suitability of health apps, and the status of eHealth readiness in the developing world. This book is a valuable contribution to the body of knowledge on current telehealth research interests and trends, and will be of interest to all those working in the field.s